Scene at Staubles Bay, Trinidad B.W.I. - (:unkn) unknown (My University, 2009)
Shows Staubles Bay located in the north-western peninsula of Trinidad during the colonial period
Black and White; Landscape
Keywords: Postcards; Trinidad and Tobago; Staubles Bay